2017
DOI: 10.1080/23279095.2017.1329146
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve is not associated with improved performance in all cognitive domains

Abstract: Cognitive reserve beneficially affects cognitive performance, even into advanced age. However, the benefits afforded by high cognitive reserve may not extend to all cognitive domains. This study investigated whether cognitive reserve differentially affects performance on cognitive tasks, in 521 cognitively healthy individuals aged 60 to 98 years (Mage = 68, SD = 6.22, 287 female); years of education was used to index cognitive reserve. Cognitive performance variables assessed attention, executive functions, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
3
34
1
1
Order By: Relevance
“…CR has been measured by factors such as premorbid intelligence quotient (IQ), years of education, complexity of occupation, and composites of hobbies and leisure activities (Jones et al, 2011). It is well known that older adults with a higher level of education show better global and detailed neuropsychological function (Thow et al, 2017;Groot et al, 2018;Gu et al, 2018;Lavrencic et al, 2018;Zhang et al, 2019;Zarantonello et al, 2020) than those with lower education levels. Healthy lifestyle, including cognitive, social, and physical activities, has also been positively correlated with global cognition (Clare et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CR has been measured by factors such as premorbid intelligence quotient (IQ), years of education, complexity of occupation, and composites of hobbies and leisure activities (Jones et al, 2011). It is well known that older adults with a higher level of education show better global and detailed neuropsychological function (Thow et al, 2017;Groot et al, 2018;Gu et al, 2018;Lavrencic et al, 2018;Zhang et al, 2019;Zarantonello et al, 2020) than those with lower education levels. Healthy lifestyle, including cognitive, social, and physical activities, has also been positively correlated with global cognition (Clare et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis conducted by Opdebeeck and colleagues (Opdebeeck et al, 2016) indicated that there are specific cognitive processes that might be related either to a composite score for CR, or to specific CR proxies (e.g., education, working activity or social activity). Furthermore, it has been found that CR is associated with working memory, verbal memory, executive functions, verbal fluency and verbal interference tasks (Lavrencic, Churches, & Keage, 2017), but no relationship has been shown between processing speed and CR. Such results only partially support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis conducted by Opdebeeck, Martyr and Clare (2016) has indicated that in healthy seniors there is an association between CR and cognitive performance in memory, executive functions, working memory, visuospatial abilities, language tasks, and with level of IQ. However, there is very little evidence on the relationship between CR and "fluid" cognitive functions (Baltes, 1999), such as processing speed and reaction times (Lavrencic, Churches, & Keage, 2017;Ritchie, Bates, Der, Starr, & Deary, 2013), episodic memory, working memory or executive functions (Thow et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The findings, suggesting that immersive exergaming may promote neuroplasticity and enhance domain-specific cognitive reserves (i.e., inhibition and task switching), also support the argument that the effects of cognitive reserve on cognitive performance may vary across individual cognitive domains. 40,41 This study has both theoretical and practical implications. Theoretically, this study adds to the literature that investigates the characteristics of exergames and improvement of executive functions.…”
Section: Exergaming Cognitive Functions 147mentioning
confidence: 98%